2022-RA-1151-ESGO Cognitive function performance in patients undergoing maximal effort cytoreduction surgery for gynecological cancer management. (20th October 2022) - Papadatou, Konstantina; Pergialiotis, Vasilios; Zachariou, Eleftherios; Rodolakis, Ioannis; Vlachos, Athanasios; Haidopoulos, Dimitrios; Rodolakis, Alexandros; Thomakos, Nikolaos
Abstract : Introduction/Background: Gynecological cancers account for approximately 20% of the 5 million estimated new cancer cases yearly internationally. More than half of these cases are surgically treated with a perioperative morbidity ranging between 2 and 40%. To date, the impact of the extent of surgical operations on cognitive functions of patients remains unknown. Methodology: We performed a prospective observational study to evaluate the burden of surgical extent (based on the Mayo Clinic classification) on perioperative cognitive function of gynecological cancer patients. Prior to inclusion in the study, we screened eligible patients for depressive disorders using the Patient Health Questionnaire-9 (PHQ-9). Identification of potential cases with severe cognitive dysfunction was assessed with the Hopkins verbal learning test. Identification and omission of cases with severe memory disability was performed with the Short Portable Mental Status Questionnaire (SPMSQ). Evaluation of differences in the perioperative cognitive performance of patients was performed with the Quick Mild Cognitive Impairment tool (QMCI). Results: Overall, 40 patients were enrolled in the study. Of those 12 patients had an intermediate complexity score, whereas the remaining had a low complexity score. None of those had severe depression (median PHQ-9 3 (2–4)) or severe cognitive dysfunction (median Hopkins scale 17 (14–19)). The SPMSQ battery tool revealed 3 cases with mild memory disability. Differences in the perioperative cognitive performance was significant between pre- and post-operative scores in all patients. The result was more evident in patients with intermediate complexity scores (presurgical score 69.5 (64.87–76.64) vs postsurgical 22 (19.75–59.25), p=.007 ) compared to patients with low complexity score (presurgical score 61 (56–65) vs postsurgical score 55.5 (46.5–63.5). Conclusion: Maximal surgical cytoreduction significantly affects the cognitive function of gynecological cancer patients. To date, relevant evidence in gynecologic oncology is scarce and efforts must be made to improve the quality of cognitive performance during the perioperative period.